1997
DOI: 10.1016/s0092-8674(00)80184-1
|View full text |Cite
|
Sign up to set email alerts
|

cAMP Activates MAP Kinase and Elk-1 through a B-Raf- and Rap1-Dependent Pathway

Abstract: Cyclic adenosine monophosphate (cAMP) has tissue-specific effects on growth, differentiation, and gene expression. We show here that cAMP can activate the transcription factor Elk-1 and induce neuronal differentiation of PC12 cells via its activation of the MAP kinase cascade. These cell type-specific actions of cAMP require the expression of the serine/threonine kinase B-Raf and activation of the small G protein Rap1. Rap1, activated by mutation or by the cAMP-dependent protein kinase PKA, is a selective acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

62
843
7

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 996 publications
(913 citation statements)
references
References 43 publications
(13 reference statements)
62
843
7
Order By: Relevance
“…In contrast to NGF treatment, epidermal growth factor (EGF) treatment of PC12 cells induced an acute phasic activation of p42 MAPkinase which returned to baseline within 30 min ( Figure 1B). These data are in agreement with data of several other laboratories [16,21,22,34,35]. Bailie et al reported that primary cultures of hepatocytes possess binding sites for NGF, and we investigated whether NGF had a similar capability to modulate the MAP kinase cascade in these cells [26].…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to NGF treatment, epidermal growth factor (EGF) treatment of PC12 cells induced an acute phasic activation of p42 MAPkinase which returned to baseline within 30 min ( Figure 1B). These data are in agreement with data of several other laboratories [16,21,22,34,35]. Bailie et al reported that primary cultures of hepatocytes possess binding sites for NGF, and we investigated whether NGF had a similar capability to modulate the MAP kinase cascade in these cells [26].…”
Section: Discussionsupporting
confidence: 90%
“…For inhibition of the Ras pathway much smaller amounts of Ras(S17N) are normally used. More likely however, the dominant negative e ect of (S17N)Rap1B observed by Vossler et al is caused by titration of another not yet identi®ed Rap-GEF, since C3G could not potentiate the cAMP-mediated activation of ERKs (Vossler et al, 1997). In another very recent paper, C3G and Rap1 were also found to be on separate pathways (Tanaka et al, 1997).…”
Section: Resultsmentioning
confidence: 95%
“…mGDP in the presence or absence of the indicated concentrations of C3G-CD after addition of 100-fold excess of unlabeled GDP. The assay was performed at 258C in 50 mM Tris, pH, 7.5, 5 mM MgCl 2 and 5 mM DTE submitting our manuscript, Vossler et al (1997) described a dominant negative e ect of (S17N)Rap1A on the cAMP-dependent activation of Elk-1. This seems to be in contrast to our data, but one explanation could be the very large amount of (S17N)Rap1B (10 mg of DNA) that was used to transfect PC12 cells as we do observe some inhibition using 10 mM (S17N)Rap1A in our in vitro assay.…”
Section: Resultsmentioning
confidence: 96%
“…Assessing total cellular Rap 1 by immunoblotting is helpful but again only semiquantitative (Posern et al, 1998). Rap 1 activation has been assessed by other methods but these require transfecting cells with a tagged-version of Rap and/or incubating cells with high amounts of 32 PO 4 (Altschuler et al, 1995;Vossler et al, 1997;Boussiotis et al, 1997). In this work we describe a quantitative method to assess Rap 1 activation which does not require manipulation of the cells and we have applied this method to cultured cells; the method can also be used to assess Rap 1 activation in tissue samples.…”
Section: Introductionmentioning
confidence: 99%